2016
DOI: 10.1111/hel.12334
|View full text |Cite
|
Sign up to set email alerts
|

Recent “omics” advances in Helicobacter pylori

Abstract: The development of high-throughput whole genome sequencing (WGS) technologies is changing the face of microbiology, facilitating the comparison of large numbers of genomes from different lineages of a same organism. Our aim was to review the main advances on Helicobacter pylori "omics" and to understand how this is improving our knowledge of the biology, diversity and pathogenesis of H. pylori. Since the first H. pylori isolate was sequenced in 1997, 510 genomes have been deposited in the NCBI archive, providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The ultimate aim for many researchers considering H. pylori genomics is the development of new therapies . Accordingly, Chaput et al .…”
Section: Helicobacter Genome Plasticity and Virulencementioning
confidence: 99%
See 1 more Smart Citation
“…The ultimate aim for many researchers considering H. pylori genomics is the development of new therapies . Accordingly, Chaput et al .…”
Section: Helicobacter Genome Plasticity and Virulencementioning
confidence: 99%
“…The ultimate aim for many researchers considering H. pylori genomics is the development of new therapies. 23 Accordingly, Chaput et al 24 studied an isogenic mutant of the amiA gene encoding a N-acetylmuramoyl-l-alanyl amidase, showing the mutant was impaired in colonizing mouse stomach. Thus, these authors suggested AmiA is a valid target for the development of new antibiotics.…”
Section: Helicobacter Genome Plasticity and Virulencementioning
confidence: 99%
“…The multilocus sequence typing (MLST), in which seven housekeeping genes (atpA, efp, mutY, ppa, trpC, ureA, and yphC) are sequenced and compared, has shown H. pylori populations to be highly structured into clusters of related lineages. 5,6 According to Bayesian cluster of the seven housekeeping genes, there are currently seven H. pylori populations, hpAfrica1, hpAfrica2, hpNEAfrica, hpSahul, hpAsia2, hpEurope, and hpEastAsia. [7][8][9] This structured population provided strong evidence of ancient ancestry in Africa and of co evolution with the human host since then.…”
mentioning
confidence: 99%
“…These new approaches enable several limitations of the previously referred to methods to be overcome and allow for a wider perspective on H. pylori biomarkers, pathogenicity and evolution. The importance and potential of whole genome data on bacterial pathogen evolution, virulence and pathogenicity has been acknowledged for over two decades [224] and we now have the technologies to get the best possible out of such data [225]. Presently (as of January 2022), a total of 2251 H. pylori genomes are recorded in the Pathosystem Resource Integration Center (PATRIC) database [226], reflecting the commitment of the scientific community to this technology (Figure 3).…”
Section: New Approaches To H Pylori Biomarker Detectionmentioning
confidence: 99%